CO2 Contrast as Alternative Media Contrast for Renal Insufficiency Patient in Angiography: An Evidence Based Case Report - Bermana, Frengky; Pratama, Dedy (UI Scholars Hub, 2021)
The use of iodine contrast, which is more commonly used, is associated with systemic effects in nephrogenic systemic fibrosis, contrast-induced nephropathy (CIN) in patients with kidney function disorders, geriatric, hypertension, and patients with comorbid diabetes mellitus and hypersensitivity reactions. An evidence-based case report was carried out in the Medical Department of Surgery, FKUI-RSCM. The study indicated that the safety of CO2 angiography did not cause CIN to manifest and showing CO2 contrast proved to be safe for patients who have impaired renal function